MICA-specific nanobodies for diagnosis and immunotherapy of MICA+ tumors - Verhaar, Elisha R.; Knoflook, Anouk; Pishesha, Novalia; Liu, Xin; van Keizerswaard, Willemijn J. C.; Wucherpfennig, Kai W.; Ploegh, Hidde L. (Frontiers in Immunology, 2024)
MICA and MICB are Class I MHC-related glycoproteins that are upregulated on the surface of cells in response to stress, for instance due to infection or malignant transformation. MICA/B are ligands for NKG2D, an activating receptor on NK cells, CD8 + T cells, and γδ T cells. Upon engagement of MICA/B with NKG2D, these cytotoxic cells eradicate MICA/B-positive targets. MICA is frequently overexpressed on the surface of cancer cells of epithelial and hematopoietic origin. Here, we created nanobodies that recognize MICA. Nanobodies, or VHHs, are the recombinantly expressed variable regions of camelid heavy chain-only immunoglobulins. They retain the capacity of antigen recognition but are characterized by their stability and ease of production. The nanobodies described here detect surface-disposed MICA on cancer cells in vitro by flow cytometry and can be used therapeutically as nanobody-drug conjugates when fused to the Maytansine derivative DM1. The nanobody-DM1 conjugate selectively kills MICA positive tumor cells in vitro.